2018
DOI: 10.1080/10826084.2018.1474226
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the Drug Normalization Framework: A Quantitative Assessment of Cannabis Use Patterns, Accessibility, and Acceptability Attitudes among University Undergraduates

Abstract: Women report lower odds of positive cannabis acceptability attitudes. While women report lower rates of recent cannabis use, gender is not a significant predictor for lifetime prevalence. Being a recent immigrant significantly predicts lower recent use, lower odds of favorable attitudes to cannabis, and reduced accessibility in comparison to students born in Canada. Longer-term immigrants do not show significant differences from students born in Canada on accessibility and acceptability, suggesting a substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
9
19
0
Order By: Relevance
“…44 It should be mentioned, however, that in the present study, a small percentage of students linked heavy use to being normal (3.7%) and to positive social attributes (11%) and these perceptions were more likely to be held by males than by females. Similar to Kolar et al, 27 we found females to have less accepting attitudes than did males towards cannabis, however, this difference was predominantly in relation to perceptions of heavy use rather than cannabis use in general. In addition, students who had more regular-using friends were more likely than were others to perceive heavy cannabis users to have positive social attributes.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…44 It should be mentioned, however, that in the present study, a small percentage of students linked heavy use to being normal (3.7%) and to positive social attributes (11%) and these perceptions were more likely to be held by males than by females. Similar to Kolar et al, 27 we found females to have less accepting attitudes than did males towards cannabis, however, this difference was predominantly in relation to perceptions of heavy use rather than cannabis use in general. In addition, students who had more regular-using friends were more likely than were others to perceive heavy cannabis users to have positive social attributes.…”
Section: Discussionsupporting
confidence: 88%
“…The current findings show that while the law does not deter cannabis use, informal controls might. Similar to international research on adult drug users [23][24][25] and students, 27 we found that, amongst a student sample in NZ, informal controls provide a threshold for normalization. Moreover, addressing the call by Kolar et al 27 to explore drug acceptability attitudes further, we were able to identify the attitudes shaping this threshold.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Other factors have recently been suggested, for example, seeing drugs as a means of achieving normal goals, such as cannabis use by athletes to enhance performance 41–43. Indicators for the normalisation of cannabis use have been prevalent in Canada for some time 34 44–46. Subsequent to reduced restriction of medical cannabis in 2014, rates of students who thought cannabis easy to access significantly increased in 2015/2016 (Y4) and rose in tandem with further deregulation 1 2.…”
Section: Discussionmentioning
confidence: 99%